The Influence of Competency and Delegation on Work Ethic and Its Impact on Dreamland Group Company Employee Performance - Wyrmand, Dustin; Setiawan, Heru (Jurnal Ilmiah Sumber Daya Manusia, 2024)
In this study, the researcher embarked on addressing a critical issue perceived to be affecting a company, namely the subpar performance of employees. The objective of this research is to examine the influence of competence and delegation on work ethics and its impact on employee performance at PT. Dreamland Group. The study was conducted using a questionnaire as the data collection instrument. Data analysis was performed using the multiple linear regression analysis technique. A census sampling method, involving all employees/population, was employed. The study encompassed 60 employees from various departments at PT. Dreamland Group, a property and construction company in the Bangka Belitung Province. The research findings indicate that competence and delegation have a positive and significant impact on employees' work ethic. Furthermore, work ethics also exhibits a positive and significant influence on employee performance. The results of this study conclude that there exists a significant positive influence of competence and delegation on work ethics, as well as a significant positive influence of work ethics on employee performance at PT. Dreamland Group.